Entanglement Measures and Their Properties in Quantum Field Theory - Hollands, Stefan (SpringerBriefs in Mathematical Physics,, 2018)
This book gives a rigorous treatment of entanglement measures in the general context of quantum field theory. It covers a broad range of models and the use of fields allows us to properly take the localization of systems into account. The required mathematical techniques are introduced in a self-contained way.